Lipid exchange at ER-mitochondria contact sites: a puzzle falling into place with quite a few pieces missing - Petrungaro, C; Kornmann, B (Elsevier, 2018)
Over the last years, the importance of inter-organelle communication has become more and more evident, attested by the fast growing number of newly-identified membrane contact sites (MCS). At MCSs two organelles are connected via protein tethers that bring them in close proximity to facilitate metabolite exchange. In this review, we will focus on the MCSs connecting the ER and mitochondria, which have been implicated in phospholipid transport. While we already know the molecular identity of some tethers, we are still far from understanding the mechanisms underlying the phospholipid transport processes. In vitro studies suggest that some proteins in MCSs are capable of transporting lipids, however only at rates that do not meet the mitochondrial lipid demand. In vivo studies are even more puzzling as it appears that many redundant lipid transport routes, involving various lipid transport proteins and various MCSs, compensate for each other when necessary. Here, we will discuss the challenges in interpreting the data on lipid transport between ER and mitochondria from in vitro and in vivo experiments by highlighting some critical aspects that might be worth addressing in the future.